Manajemen Pemasaran Produk Halal di Era Digital: Akses Informasi, Sikap Konsumen, dan Strategi Digital - Rahmi Pamel; Khairulis Shobirin; Nuryanti; Muhammad Deni Putra; Dailani Ismail (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This study examines the intersection between digital technology and the halal industry, focusing on three main questions: how digital technology affects the accessibility of halal product information, what are the public attitudes toward halal products in a digital context, and how digital marketing strategies can enhance awareness and trust in halal products. The novelty of this research lies in its integrative approach, combining three theoretical frameworks, Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), and Maqaṣid al-Sharīʿah, to comprehensively analyze the dynamics of digital transformation in the halal industry. Using a qualitative literature review method with thematic analysis of academic sources from Scopus, Web of Science, and Google Scholar databases (2015-2026), this study finds that blockchain technology and mobile applications significantly improve transparency and traceability in halal supply chains, yet their effectiveness depends heavily on consumer digital literacy and trust. Public attitudes toward halal products are shaped by a combination of knowledge, religiosity (β = 0.266), and subjective norms (β = 0.234), with social media influencers playing a crucial mediating role. Effective digital marketing strategies integrate halal certification, educational content, and influencer collaborations. This study contributes to the discourse on halal industry digitalization by demonstrating that technology is not a standalone solution but requires a holistic approach encompassing education, regulation, and adaptive marketing strategies.